Kağıt ve karton üretiminde iç tutkallamada kullanılan asa emülsiyonun optimizasyonu - Doğan, Duygu Özlem (2019)
In paper and paperboardmaking, internal sizing is used for making the end product more resistant to liquid penetration. Rosin, Alkyl Ketene Dimer (AKD) and Alkenyl Succinic Anhydride (ASA) internal sizing agents exist for this purpose. ASA is added to the papermaking process in the form of an emulsion. The dispersion of ASA, water, and an emulsifier are mixed under shear forces to create the capsulation and emulsion